Cellular Internet of Things: Principles, Potentials and Use Cases - Routray, Sudhir; Mohanty, Sasmita (EAI Endorsed Transactions on Internet of Things, 2024)
Internet of things (IoT) can either be deployed over existing cellular networks or their own custom-built standalone networks. Based on the infrastructure, IoT can be classified into two types: cellular and non-cellular categories. In the cellular form, IoT network needs the support of cellular infrastructure of the mobile service providers. Currently, three forms of cellular IoT are being deployed across the world. They are: narrowband Internet of things (NBIoT), extended coverage GSM (EC-GSM) and long term evolution for machines (LTE-M). Out of these three, NBIoT and EC-GSM are low energy and low resource consuming versions of cellular IoT. They need narrow bandwidths for their operations. Their energy consumption is also very low and thus suitable for low energy applications. Both NBIoT and EC-GSM are compatible with all types of cellular communication infrastructure such as 2G, 3G, 4G and 5G. They can cover a large area with a very small amount of power. Both these forms are popular low power wide area (LPWA) technologies. Due to their LPWA features, they are popular for the connected living applications at home and workplace surroundings. Their LPWA features make them popular green technology for digital transformation. LTE-M uses comparatively larger bandwidth and higher power. It is suitable for higher bandwidth and higher data rate applications. We survey the recent literature on cellular IoT and present their key principles, potentials and applications. We provide their main characteristics, deployment options, standards, and some specific applications in different sectors.